Poetry, Photography, Painting Stephanie Bolster's World - Compton, Anne (Studies in Canadian Literature / Études en littérature canadienne, 1999)
Stephanie Bolster elaborates on her writing process for White Stone, discussing publishing issues, various characters, and the length of time it involved. She discusses in detail the relation between the main character, Alec Liddell and Alice in Wonderland. She also relates information about her writing influences and her photography.